Children’s vocabulary frequently used at the end of the 20th and the beginning of the 21st century. A few comparative remarks - Święcicka, Małgorzata (Papers in Linguistics, 2022)
The aim of this paper is to characterize words statistically frequent in the vocabulary of preschool children of the end of the 20th and the beginning of the 21st century. The proposed comparative description proves the durability of children’s vocabulary often used over a period of more than thirty years. The stability of children’s vocabulary is manifested both in the identical representation and hierarchy of particular functional classes, and in the persistence of representative semantic categories. The observed status quo is determined by features of the natural language, the developmental qualities of the child’s speech and the benchmarks of the spoken style. One might say that the unchanged, grammatical and semantic, structure is accompanied by the variability of linguistic exponents in the internal structure of classes and semantic categories. This, in turn, is motivated by a number of both intralinguistic and extralinguistic processes, including civilization and cultural transformations, the development of new technologies, the phenomenon of linguistic fashions or a wider social reach of vulgar words.